Exploring Travel Medicine Perspectives among Primary Care Physicians in Kurnool District: A Comprehensive Study of Knowledge, Attitudes, and Practices - Rajesh Raja Satharla; Hindustan Abdul Ahad (Archives of Medicine and Health Sciences)
Background and Aim: The study’s purpose is to improve the quality of care for both local residents and travelers in the Kurnool district by identifying and addressing gaps and barriers. The main objective of the research was to assess the knowledge, attitudes, and practical implementation of travel medicine among primary health-care physicians working in the Kurnool district. Materials and Methods: The research utilized a descriptive cross-sectional study design. A total of 397 primary care doctors in the Kurnool area participated. Data were collected through a self-administered questionnaire, which covered sociodemographic factors, travel medicine knowledge, attitudes, and practices. Results: The study revealed that a significant portion (around 79.5%) of the participants reported providing travel health advice at some point. The primary source of information on travel medicine for most participants (66%) was the Ministry of Health’s travel guides. However, the study identified a knowledge gap, as 11.4% of individuals were unaware of the origin of typhoid infection. The most common health issues reported during posttrip consultations were diarrhea and respiratory infections. Conclusion: The study’s findings suggested that the general practitioners in the Kurnool district had insufficient knowledge, attitudes, and practices concerning travel medicine. This underscores the need for additional education and training in travel medicine to improve traveler health care and reduce the risk of preventable diseases.